2023
DOI: 10.1111/maps.14043
|View full text |Cite
|
Sign up to set email alerts
|

The bulk mineralogy, elemental composition, and water content of the Winchcombe CM chondrite fall

Abstract: On the microscale, the Winchcombe CM carbonaceous chondrite contains a number of lithological units with a variety of degrees of aqueous alteration. However, an understanding of the average hydration state is useful when comparing to other meteorites and remote observations of airless bodies. We report correlated bulk analyses on multiple subsamples of the Winchcombe meteorite, determining an average phyllosilicate fraction petrologic type of 1.2 and an average water content of 11.9 wt%. We show the elemental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…However, it should be noted that, as observed in this study, the and Bennu than for the carbonaceous chondrite samples studied in the laboratory. This may be due to differences in particle size distribution, mineralogy (e.g., sulfide content, Bates et al, 2022;Bland, 2004;Howard et al, 2010;King et al, 2015), the functions used within the Hapke BRDF model, or-as suggested by Tatsumi et al ( 2020)-due to increased space weathering, thermal processing, or ratios of organic materials present on the asteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that, as observed in this study, the and Bennu than for the carbonaceous chondrite samples studied in the laboratory. This may be due to differences in particle size distribution, mineralogy (e.g., sulfide content, Bates et al, 2022;Bland, 2004;Howard et al, 2010;King et al, 2015), the functions used within the Hapke BRDF model, or-as suggested by Tatsumi et al ( 2020)-due to increased space weathering, thermal processing, or ratios of organic materials present on the asteroids.…”
Section: Discussionmentioning
confidence: 99%
“…For a detailed description of how grain size distribution may affect the BRDF, see Cloutis et al (2013). Modal mineralogy for this sample was determined using X-ray diffraction (XRD) and was presented in Bates et al (2022).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Jenkins 2023) investigate the terrestrial alternation of the meteorite finding that surface sulfates, fusion crust calcite, and halite all post-date Winchcombe's entry into the Earth's atmosphere, indicating how rapidly meteorite falls can be terrestrially altered. Bates et al (2023) report on the correlated bulk analyses on multiple subsamples of the Winchcombe meteorite, including the modal mineralogy, infrared spectral parameters, water content, elemental composition, iron distribution, and iron oxidation state. Curtis et al (2023) measured the bidirectional reflectance distribution function of the Winchcombe meteorite across a range of viewing angles to provide a method of comparison with other meteorites, to produce Hapke parameter values used to provide a reference photometry dataset for current and future asteroid missions.…”
mentioning
confidence: 99%